The effect of waste sulfur obtained during biogas desulfurization on the availability of selected trace elements in soil - Bobowiec, Aneta; Tabak, Monika (Geology, Geophysics and Environment, 2018)
Research concerning the effect of the application of waste sulfur pulp (doses: 10, 20, 30, 60 mg S • kg–1 d.m. of soil) on selected soil properties was carried out. The pulp contained sulfur in the elemental form. Before setting up the experiment, the soil had a slightly acid reaction (determination in 1 mol • dm–3 KCl) and was not contaminated with heavy metals. After conducting the incubation experiment, it was observed that the application of sulfur pulp led to a statistically significant (and proportional to the dose) increase in the content of available sulfur in soil. Application of waste caused a decrease in soil pH and an increase in the mobility and availability of Zn, Cd and Mn (extracted with 0.01 mol • dm–3 CaCl2). In relation to soil without waste, more Zn, Cd and Mn (by 4–51%, 9–24% and 0.1–31%, respectively) was determined. Liming reduced the acidifying effect of the introduced waste – after 150 days, only soil with the highest dose of sulfur pulp was characterized by a statistically significantly lower pH than the soil without the waste addition. An increase in the rate of sulfur oxidation was also observed – after 150 days of the experiment, more sulfate sulfur (by 14.4–34.5%) was determined, with respect to treatments of the unlimed series. A considerably lower content of Zn, Cd and Mn was determined in the limed soil than in the unlimed one. Regardless of waste dose and date of analysis, the soil contained a trace content of mobile forms of Cu, Cr, Ni and Pb.